A contribuição dos atores na trajetória de formalização das agroindústrias familiares rurais em Jaguari-RS e Chapecó-SC - Deon, Paulo Roberto Cecconi (2015)
The formalization of Rural Family Farming (RFF) is understood here as a complex process‟, because it is suit industry standards an activity that once served as household value and whose features handmade become valued by consumers as differentiated products for industrial products. The literature suggests that the viability of this possibility marketing involves the organization of farmers, with the action of different actors, to promote cooperation among stakeholders. It is characterized, therefore, an economic phenomenon that is inserted‟ in a context of internal social relations family, but also relationships that constitute the external actors with expertise, for specific socio-spatial to the issue. These are variables that make up the institutional environment in which RFF are immersed and shape the study of the problem that arises in order to understand how Rural Family Farming are formalized, featuring actors and the relationships that are established to overcome the adversities that the institutional environment exerts on those experiences. Thus, this study aims to analyze the dynamics inherent in the formalization of Rural Family Farming, trying to understand the contribution of the actors to overcome adversity related to the institutional environment. The theoretical orientation of the research is located predominantly in the tradition of the New Economic Sociology. We used the method of comparative study of cases‟, the analytical units are located in the municipalities of Jaguari-RS and Chapecó-SC. Data collection was conducted from secondary sources (bibliographies and databases), but mostly from primary sources (interviews, documents and free observation) with farmers and the actors with whom they relate on the basis of projects of RFF, using specific instruments (scripts semi-structured) for each category. We used a qualitative approach, supported occasionally by quantitative methods (frequency distribution), where the organization of the information collected was to enable the analysis of content, supporting the interpretations based on the theoretical framework presented. The results call into question the effectiveness of the ways in which family farming is organized and is represented, as well as their own support services to overcome barriers to the institutional environment (especially with regard to the requirements of the existing legal framework) imposes on projects of family farming. The study suggests that advances in potential do not occur by the individual action of farmers, either by deterministic State action, but as a construction carried out by farmers' organizations, supported decisively by their forms of representation, by organizations of social movements and the government.